Entre a interpretação e o trauma: os desafios do setting no cuidado aos estados-limite - Cardoso, Lígia Maria Ananias (2025)
This thesis focuses on the discussion of clinical conduct in psychoanalysis with individuals marked by traumatogenic experiences. These are stories that reflect forms of suffering related to the archaic, in which early trauma and helplessness contribute to inconsistencies in the development of the limits of the Self. It follows that analysis is crossed by the effects of traumas prior to the constitution of the Ego, requiring listening to manifestations that fall short of the subject's symbolic capacity. This implies a subjective position ― on the part of the analyst ― that reverberates in the management of transference, countertransference and the framework. In this study, we seek to bring the borderline states clinic to the agenda, addressing the complexities derived from the analytical encounter with regard to such management and the adaptation of the setting. The aim is to reflect on the interpretative psychoanalytic technique and on the importance of care practices that are relevant to the needs and possibilities of these subjects.Based on the psychoanalytic method, this research is built on three strands that intertwine theory and clinic, anchored in the conceptual contributions of Freud, Ferenczi and Winnicott: the first is dedicated to revisiting the notion of trauma, marking the distinctions between each of the theorists; the second contextualizes the historical construction of Freudian practice, going from the “prehistory” of psychoanalysis to the discovery of the phenomenon of transference; and the third strand discusses the technical conceptions in each of the aforementioned authors, also drawing inspiration from other contemporary psychoanalysts. Theory and technique are interspersed with clinical cases, linking them to the problems of borderline states. Through the reflections proposed, we come up against the limitations of interpretative-associative methods in this field of psychopathology, and consider the relevance of personalizing the setting, based on the active and impulsive presence of the analyst